Pengaruh Promosi terhadap Keputusan Menggunakan Grabfood (Studi Kasus pada Mahasiswa Universitas Batanghari) - Riko Mappadeceng; Pupu Sopini; David Gionola (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
In an effort to influence the market to make purchasing decisions, promotional activities (promotional mix) are a better strategy combination, and are entirely planned to achieve sales objectives. Promotion is a form of direct persuasion through the use of various incentives that can be arranged to stimulate immediate purchase or increase the number of goods or use of services by customers or consumers. The research method used in this research is descriptive and quantitative methods. The student population is all Unbari University students, totaling 4,888 people and a sample of 98 people. Based on the results of the research, an overview of promotions, including gifts given, gets the attention or interest of consumers, meaning that sales promotions in the form of gifts are important and one of the things that can influence the decision to use GrabFood. At GrabFood, these prizes can be in the form of promo vouchers and so on. As for the description of the decision to use GrabFood, consumers are interested in buying back in the future which is included in the individual commitment indicator. Furthermore, the results of the study indicate that the results of the t test produce a significance value of 0.000. The coefficient of determination test obtains an Adjusted R Square value of and the results of a simple regression test produce the following regression equation: Y = 23,492 + 0,313 X So it can be concluded that the results obtained indicate that the promotion of GrabFood has a significant positive influence on the decision to use GrabFood for students at Batanghari University Jambi.